Jurisdiction Of A Country’s Air Territorry In International Law Perspective - Yan Jefri Barus (Institute Of computer Science (IOCS), 2021)
The sovereignty of a country is no longer absolute or absolute, but at certain limits it must respect the sovereignty of other countries, which are regulated through international law. This is what became known as the relative sovereignty of the state. In the context of international law, a sovereign state must essentially obey and respect international law, as well as the sovereignty and territorial integrity of other countries. The problem in this research is How is the JURISDICTION of a country's airspace? What are the principles of air law adopted by nations in the world (internationally)? How is the JURISDICTION of a country's airspace in the perspective of international law? Its basic function is to show the way to solve research problems. The airspace contained above the land area, inland waters, and territorial sea is included in the jurisdiction of a country. This can be seen from article 1 of the Chicago Convention 1944 concerning International Civil Aviation: